Eksplorasi Fermentasi Kimchi Rebung Pada Pembelajaran Kimia Bahan Pangan Berbasis Inkuiri - Nurdianti Awaliyah; Tuti Kurniati; Frestika Dania Yanti (Entalpi Pendidikan Kimia, 2026)
Bamboo shoots are one of the abundant natural resources in West Kalimantan. Their potential as a fermented food is considerable because they contain carbohydrates similar to those found in napa cabbage, the primary ingredient used in kimchi. This study aimed to determine the product assessment of the taste, aroma, and texture of bamboo shoot kimchi in food chemistry learning using an inquiry-based approach. The inquiry stages included problem formulation, formulation of experimental objectives, hypothesis development, collection of data on tools, materials, and procedures, data analysis, and drawing conclusions. The research employed a quantitative descriptive method to describe the quality of bamboo shoot kimchi products and compare them with napa cabbage kimchi produced by students in inquiry-based food chemistry learning. The product evaluation results indicate that bamboo shoot kimchi has a high level of similarity to napa cabbage kimchi in terms of texture, while the similarity in aroma is moderate and the similarity in taste is low.